Learner Career Evaluation in a Quasi-rural Area of South Africa - Annelize Potgieter Mrs; John Dunlevey Prof (Educational Considerations, 2025)
Although much has been written by educationists about career guidance and subject selection by learners in South African schools, this appears to be largely based on theoretical domains and academically derived socio-political goals, with little input from the subject teachers and virtually none from the different categories of learners. Therefore, as part of a University of Limpopo and Rotary (Pietersburg 100 Club) outreach program, Grade 9 learners were surveyed in the town of Mankweng, some 30km east of the city of Polokwane. Although in several ways the results presented herein confirmed the expected (predicted) gender and cultural divides, there are certain trends that indicate a break from purely traditional stereotypes.
Keywords: quasi-rural; Mankweng; learner perception; career evaluation; age and gender; Helper; Persuader; Organiser; Doer; Thinker; Creator